Analyzing foreign policy - Beach, Derek; Pedersen, Rasmus Brun, 1978- (London : Macmillan International Higher Education : Red Globe Press, 2020)
Genuinely international in scope and drawing on a wide range of examples from around the world, this major new introduction to foreign policy analysis focuses on the key explanatory factors that underlie the foreign policies of states and other actors to show how theory can illuminate practice.
Introduction: Analyzing Foreign Policy -- Research Questions and the Use of Theory -- Choosing an Appropriate Research Strategy -- System-Level Factors -- Domestic Factors -- Understandings of the Choice Situation -- Making Foreign Policy Decisions --What States Do: Security Policies -- What States Do: Diplomacy -- What States Do: Economic Foreign Policies -- A Transformation of State Foreign Policy-Making?
Previous edition: Basingstoke: Palgrave Macmillan, 2012.
Includes bibliographical references and index.
Keywords: International relations